Immortal Ozurdex: A 10-month follow-up of an intralenticular implant - B Poornachandra; Vinod B M Kumar; Chaitra Jayadev; Subashchandra H Dorelli; Naresh Kumar Yadav; Rohit Shetty (Indian Journal of Ophthalmology, 2017)
A 78-year-old male who had received a dexamethasone implant (Ozurdex, Allergan, Inc., Irvine, CA, USA) 15 days back for recalcitrant diabetic macular edema in the left eye came to us for a second opinion. On examination, his corrected distance visual acuity was 20/20 in the right eye and 20/40 in the left eye. Early cataractous changes were present in both eyes. The intraocular pressure was within normal limits. The Ozurdex implant was seen lodged in the posterior cortex of the crystalline lens in the left eye, confirmed on anterior segment optical coherence tomography (OCT) and ultrasound biomicroscopy. Fundus examination showed moderate nonproliferative diabetic retinopathy in both eyes with macular edema and epiretinal membrane in the left eye, confirmed on OCT. The patient was noncompliant and returned after 10 months. Interestingly, the implant was still present in the same location with the same vision and anterior segment findings as before. The OCT showed a reduction in macular edema. The patient was advised regular follow-up and cataract surgery at a later date.